Ultra-high heating rate effects on the sintering of ceramic nanoparticles: an in situ TEM study - Xin Li Phuah; Jie Jian; Han Wang; Xuejing Wang; Xinghang Zhang; Haiyan Wang (Materials Research Letters, 2021)
Heating rate plays a major role in the ceramic sintering process, especially in many new advanced sintering techniques. In this study, the effects of ultra-high heating rate up to 1200°C/s have been investigated on various ceramic nanoparticles by in situ transmission electron microscopy (TEM) heating experiments to monitor the morphological changes immediately after the heating process and during the holding time. It was revealed that an ultra-high heating rate is highly effective in densifying 3 mol.% yttria-stabilized zirconia nanoparticles but was less effective for 8 mol.% yttria-stabilized zirconia or zinc oxide due to the competing diffusion mechanisms.